The Simpsons : Treehouse Of Terror - Silverman, David, 1957-; Azaria, Hank.; Harry Shearer; Julie Kavner; Marcia Wallace; Nancy Cartwright (USA 20th Century Fox Television, 1989)
The Simpsons are very politically incorrect family. Homer works with pride in a nuclear power plant run with more regard for profit that safety. His wife is Marge, a kind of supermom. They have three kids: Bart, an underachiever (""and proud of it""), Lisa (who is as serious and responsible as Bart isn't), and Maggie.
The satiric adventures of a working class family in the misfit city of Springfield.
Language(s): English, French, German Subtitle(s): French, Dutch, Swedish, Hungarian,Nnorwegian, Danish, Finnish, English
Keywords: Comedy -- Animation -- Tv Series